European Commission merger decisions: 1999-2006 - Garrod, Luke (UK Data Service, 2015)
This dataset is constructed from merger decisions of the European Commision which were notified between 1999 and 2006 inclusive. The primary source of data is the standardised decision reports published by the EC for each merger decision. The ESRC Centre for Competition Policy (CCP) at the University of East Anglia (UEA) undertakes interdisciplinary research into competition policy and regulation that has real-world policy relevance without compromising academic rigour. It prides itself on the interdisciplinary nature of the research and the members are drawn from a range of disciplines, including economics, law, business and political science. The Centre was established in September 2004, building on the pre-existing Centre for Competition and Regulation (CCR), with a grant from the ESRC (Economic and Social Research Council). It currently boasts a total of 26 faculty members (including the Director and a Political Science Mentor), 4 full- and part-time researchers and 23 PhD students.